Manfaat Vessel Traffic System (VTS) di Alur Pelayaran Tanjung Emas Semarang - Karolus Geleuk Sengadji; Mustholiq; Dimas Satria Hemarnaswa; Ariska Hendra Jaya (Politeknik Ilmu Pelayaran Semarang, 2021)
This study aims to determine whether the Vessel Traffic System (VTS) in Tanjung Emas is sufficient to provide benefits to users of port facilities. This research was conducted to determine whether the implementation of VTS as a form of technological advancement (science and technology) in the maritime world has been fully enjoyed by shipping service users. In obtaining data and filling out the questionnaire in this study using a sample of 60 people from the shipping office and ship crew (ABK). The research method is descriptive qualitative method and the sampling technique in this study is non-probability sampling with purposive sampling method. Based on the research results it can be concluded that VTS service users are satisfied with the services provided to vessels. The information system owned by VTS Tanjung Emas is quite effective in providing information related to shipping in Tanjung Emas. VTS gives a sizable economic role to the state through PNBP payments.